2019
DOI: 10.15288/jsad.2019.80.149
|View full text |Cite
|
Sign up to set email alerts
|

Public Health Surveillance Studies of Alcohol Industry Market and Political Strategies: A Systematic Review

Abstract: Objective:This review examines public health surveillance (PHS) studies of alcohol industry actors that explore the implications of the integration of business and political strategies for public health.Method:Eligible for inclusion were studies published in English language peer-reviewed journals since 1980 that sought to investigate both alcohol industry business and political strategies and their implications for public health. Studies were also required to present economic, political, and health data toget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…Recent studies have identified how tobacco industry actors employ highly integrated global strategies to shape policy environments and engage in processes of venue shifting within multi-level governance systems (Hawkins et al, 2018, 2019). Given the similarities identified elsewhere between the market and political strategies of the global tobacco and alcohol industries, it is likely that alcohol industry actors adopt similar approaches in this regard (Hawkins et al, 2016; McCambridge et al, 2019a, 2019b).…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have identified how tobacco industry actors employ highly integrated global strategies to shape policy environments and engage in processes of venue shifting within multi-level governance systems (Hawkins et al, 2018, 2019). Given the similarities identified elsewhere between the market and political strategies of the global tobacco and alcohol industries, it is likely that alcohol industry actors adopt similar approaches in this regard (Hawkins et al, 2016; McCambridge et al, 2019a, 2019b).…”
Section: Methodsmentioning
confidence: 99%
“…Each step was guided by the growing number of CDOH frameworks which identify and categorise the strategies used by corporations. 2,17,18,[29][30][31][32][33][34][35][36] Quantitative Data Collection and Analysis Market share data (percentage of market sales attributed to a global company) were sourced from the Euromonitor Passport Database for the world's largest 80 markets for the years 2011-2019. Market sales volume data (kg) were sourced from the same database for the years 2006-2019, with projections to 2024, for UPF and UPB categories.…”
Section: Methodsmentioning
confidence: 99%
“…As markets in HICs begin to stagnate, Big Food is moving to pursue growth opportunities in UMICs and LMICs, attracted by their large, growing and increasingly urbanised populations whose incomes are rising. 6 Strategies Used to Establish, Promote, and Sustain High Levels of UPF Consumption Whilst there have been many different categorisations of the corporate playbook used to establish and promote UPF consumption, 17,18,[29][30][31][32][33][34][35][36]44 we broadly categorised these strategies into market practices and political practices. These practices are defined as applied business strategies and tactics employed to advance a corporation's economic performance and create a more favourable external environment.…”
Section: Global Trends and Dynamics In Upf Marketsmentioning
confidence: 99%
“…The alcohol industry has a vested interest in how governments respond to alcohol-related harms McCambridge, Coleman, et al 2019 (Hawkins and McCambridge 2020). This might be important to understanding how industry actors exercise their power.…”
Section: Alcohol Public Health and Policymentioning
confidence: 99%